2022
DOI: 10.3389/fendo.2022.973452
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in risk of contrast-induced nephropathy in patients with chronic kidney disease and diabetes mellitus by enhanced external counterpulsation

Abstract: ObjectiveTo evaluate the efficacy of enhanced external counterpulsation (EECP) in the prevention of contrast-induced nephropathy (CIN) in patients with combined chronic kidney disease (CKD) and diabetes mellitus (DM) by comparing the changes in renal function-related indicators in patients before and after coronary angiography (CAG) or percutaneous coronary intervention (PCI).MethodsThere were 230 subjects consecutively included in the study. Of these, 30 cases with DM underwent rehydration therapy, and 200 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Zeng et al [ 24 ] explored this protective effect of EECP in patients with chronic kidney disease (CKD) with or without diabetes mellitus receiving intra-arterial contrast in coronary angiography procedure, who had high risk for contrast-induced kidney injury. Unlike the previous study, the authors applied two EECP sessions, one before the procedure and the other after radiocontrast exposure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeng et al [ 24 ] explored this protective effect of EECP in patients with chronic kidney disease (CKD) with or without diabetes mellitus receiving intra-arterial contrast in coronary angiography procedure, who had high risk for contrast-induced kidney injury. Unlike the previous study, the authors applied two EECP sessions, one before the procedure and the other after radiocontrast exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The postoperative estimated GFR was increased in those receiving EECP therapy (44.0 ± 15.6, compared with 41.5 ± 12.7 mL/min/1.73 m 2 , P = 0.047). The incidence of contrast-induced kidney injury was significantly lower with EECP therapy (3.8%, compared with 16.7% in those receiving standard 0.9% NaCl hydration alone, P -value 0.042) along with lower high-sensitivity C-reactive protein, possibly reflecting reduced renal inflammation from contrast media [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 EECP therapy has also been shown to reduce the risk of contrast-induced nephropathy in patients with T2DM with CAD undergoing coronary angiography or percutaneous coronary intervention. 22 A few small studies have suggested the beneficial impact of EECP therapy on transcranial Doppler middle cerebral artery flow velocities and National Institutes of Health Stroke Scale scores in patients with acute ischaemic stroke. 23,24 The impact of EECP therapy on other macrovascular and microvascular complications of diabetes is not known and remains an important area of future research.…”
Section: Discussionmentioning
confidence: 99%
“…As the exploration of mechanisms deepens, the effects of EECP including inhibition of oxidative stress, anti-inflammation, vasculogenesis and angiogenesis have been recently revealed ( Shen et al, 2020 ). Subsequently, studies of EECP have broadened in conditions like type 2 diabetes, erectile dysfunction, and psychiatric diseases ( Springer et al, 2001 ; Raeissadat et al, 2018 ; Zeng et al, 2022 ). It is important to learn more about the effects of EECP and to explore potential mechanisms that will lead to optimized therapy and aid prognosis.…”
Section: Introductionmentioning
confidence: 99%